Relationship between physical activity and hypertension in adults in the working area of Puskesmas Tampaksiring I - Wacika, Dewa Ngakan Gede Sathyananda; Permatananda, Pande Ayu Naya Kasih; Suyasa, Eka Ariawan (Universitas Muhammadiyah Surabaya, 2024)
Hypertension, often known as high blood pressure, is characterized by systolic blood pressure of at least 140 mmHg and/or diastolic blood pressure of at least 90 mmHg. Lack of regular physical activity is one of the risk factors for hypertension. This study aims to analyze the relationship between physical activity and the incidence of hypertension in adulthood. This study employs a cross-sectional design and analytical observational research methodology. The number of subjects in the study were 62 hypertension subjects and 62 non-hypertension subjects. Data was collected with the IPAQ-SF questionnaire to determine the level of physical activity. Data analysis was performed using the Chi-square statistical test. The results of the univariate analysis showed that the majority of research subjects were aged 41-60 years (53.2%), female (66.9%), and 91.5% of subjects with hypertension were classified as having low physical activity. There was a strong correlation between physical activity and the incidence of hypertension, as shown by the bivariate analysis, which yielded a value of p = 0,00 (p 0,05). The conclusion of this study was that there is a relationship between physical activity and the incidence of hypertension in adulthood in the working area of Tampaksiring I public health center.